Natural orifice transluminal endoscopic surgery in gynecology - Chyi-Long Lee; Kai-Yun Wu; Hsuan Su; Pei-Ju Wu; Chien-Min Han; Chin-Jung Wang; Chih-Feng Yen (Wolters Kluwer Medknow Publications, 2012)
Objective: To present our initial experiences in transvaginal natural orifice transluminal endoscopic surgery (NOTES) for adnexal surgeries and hysterectomies. Materials and Methods: From September 2010 to December 2010, a total of 15 patients with benign adnexal or uterine diseases who were eligible for laparoscopic surgeries were recruited to undergo transvaginal NOTES at a tertiary referral medical center. Intraoperative and postoperative surgical outcomes were measured. Results: Transvaginal NOTES was successfully completed in five adnexal surgeries and 10 hysterectomies without complications, an ancillary port on the abdomen, or conversion to conventional laparoscopy or laparotomy. For the 10 hysterectomies, the surgical time was 93.4 ± 6.3 minutes (mean ± standard deviation), intraoperative estimated blood loss 245 ± 54.0 mL, uterine weight 440.1 ± 76.5 g, and the postoperative hospital stay 2.7 ± 0.3 days. No patients required intraoperative blood transfusion. The two tubal sterilizations were completed in 18 minutes and 30 minutes, respectively, with negligible blood loss. The two salpingectomies, including one ruptured ectopic pregnancy with 2000 mL hemoperitoneum, were completed in 62 minutes and 116 minutes, respectively. The enucleation was completed in 64 minutes with 20 mL estimated blood loss. Conclusion: Our preliminary results indicate that transvaginal NOTES for adnexal surgeries and hysterectomies is feasible and safe. However, this procedure is still new and should only be used as an alternative for conventional laparoscopic surgery in highly selected cases.